Anxiety-Depressive Disorders In Patients With Heart Failure: Development And Treatment (Eurasian Research Bulletin, 2024)
The aim of the study was to determine the presence and severity of anxiety-depressive experiences and to assess their impact on the quality of life in patients with acute heart failure with a history of large-focal (Q-wave) myocardial infarction.